OP0347-HPR Training rheumatology nurse specialists: what does the future hold?. (15th June 2017) - Nisar, MK; Begum, J
Abstract : Background: Since the introduction of the Rheumatology nursing in the UK in 1980s, there has been gradual development of the "specialty". Despite the proven benefits, both clinical and economical, of a well-trained rheumatology nurse specialist and the evolution of the role, there is a lack of a clear career path for the profession. Objectives: We undertook a pilot survey to understand the present climate of rheumatology practitioner training in the region. Methods: Following a focus group discussion of an "ideal" development route for rheumatology practitioners, ten items were unanimously identified as areas for job progression. These included appropriate induction, prescribing skills, involvement in research and education, opportunities for combined working and scope for clinical development. A questionnaire was created based on these items and mailed to all the rheumatology units in the East of England. Replies were compiled to ascertain the current picture of regional training. Results: There are 19 centres providing rheumatology services in the region with 51 rheumatology practitioners. All of them (100%) replied to the questionnaire. Only four units (21%) provide formal induction programme for training. 11/19 (57%) have nurse prescribers. All providers replied positive to the question pertaining nurses' participation in research and audit; 12 (63%) have presented locally or nationally and eight (42%) have submitted posters to conferences. 12 centres have partly nurse delivered early arthritis pathway and 13 have access to departmental ultrasound. Ten units provide patient educational events. Conclusions: This is a pioneering survey outlining access of rheumatology practitioners and nurse specialists to developmental opportunities. This initiative highlights a wide variation in the provision of clear career pathway regionally. Though most centres are delivering contemporary services, these are not being used effectively for developing key team members. There is lack of formal induction programme. Though most nurses are involved in audit, less than a quarter are presenting at any level and even fewer are publishing research endeavours. Prescribing is limited to 15/51 (29%) members. Less than 20% are training to do intra-articular injections or learning musculoskeletal ultrasound. Despite patient education being a core skill for this group, only 10 units deliver these as a formal event. In conculsion, there is wide variation in the provision of career advancing opportunities to rheumatology nurse specialists. This can potentially have a negative impact on staff recruitment and retention. There is a need for improving standards and delivery of rheumatology professionals' career development. Disclosure of Interest: None declared